Should the US Government have Bailed Out Lehman Brothers? - Creed, Scott (2010)
This research provides an analysis of whether the US government should have bailed out Lehman Brothers in the midst of the recent financial crisis. Both quantitative and qualitative factors have been analysed in order to bring together the numerous issues that surrounded the government’s monumental decision to allow Lehman Brothers to face bankruptcy. Comparisons have been made with other financial institutions who received financial support from the Federal Reserve to attempt to see if there was any outstanding rationale behind the decision.